The Level of Knowledge and Decay Missing Filling -Teeth (DMF-T) Index in Children Aged 12-15 years old in Coastal Area of Southeast Minahasa Regency Indonesia - Tahulending, Anneke A.; Adam, Jeanne d’arc Z.; Ratuela, Jeineke; Sumampouw, Oksfriani J. (Newinera Publisher, 2023)
Plaque is a soft layer of a collection of bacteria and sticky that adheres to teeth. One of the efforts to control it is to brush your teeth regularly and regularly use mouthwash. Currently, many mouthwashes have been developed with traditional plant ingredients that have antiseptic and antibacterial properties with side effects. One of these traditional plants is Green Tea (Camellia sinensis) and Nutmeg (Myristica fragrans Houtt). The purpose of this study was to analyze the effect of gargling with steeping green tea (C. sinensis) and nutmeg (M. fragrans Houtt) on the decline in plaque index of adolescents aged 17-19 years. The type of research used is quasi-experiment research one group pre-post test. This research was conducted in October-December 2022. The subjects of this study were Polytechnic students of the Ministry of Health of the Republic of Indonesia Manado aged 17-19 years and willing to be research subjects. The number of samples obtained in this study was 42 people. The treatment given is gargling with steeping green tea (C. sinensis) and nutmeg flowers (M. fragrans houtt). The variable measured is the plaque index. This research instrument uses diagnostic tools and plaque index assessment format. The data obtained were analyzed using a paired sample t-test statistical test. The results of this study showed that the average plaque index before gargling steeping green tea (C. sinensis) was 2.09 and after that was 1.35, had a difference in decrease of 0.74 points. The average plaque index of steeping nutmeg (M. fragrans houtt) before was 2.03 and after that was 1.03, had a difference of 1.00. Based on analysis using paired sample t-test shows there is a significant difference seen from the value of p = 0.00 (0.00<0.05). It can be concluded that the gargling with steeping green tea (C. sinensis) and nutmeg flowers (M. fragrans houtt) can make the plaque index of adolescents aged 17-19 years better.